Racism and trust in Europe - Matthew Bonick (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2021)
I study the impact of racism on trust in Europe. To operationalize trust and racism, I use individual level responses from the European Social and World Value Surveys. The results of the multivariate analysis indicate, individuals who possess a self-reported racist attitude are less likely to be trusting. To address the issue of causality, I examine second generation immigrants. When analyzing immigrants and using the level of racism of their origin country as a proxy for individual racial attitudes, I find, racism continues to predict lower levels of trust. These results provide evidence racism has a negative, significant, and causal impact on generalized trust. Additionally, the paper supports the notion that racism could have negative economic consequences via the erosion of social capital.
Keywords: O1; Z1; 330; Racism; Trust; Culture